Larceny in the product market: A hidden tax? - Osborne Jackson; Thu Tran (Federal Reserve Bank of Boston, 2020)
This paper compares the distortionary impact of larceny theft across different product markets, characterizing such crime as a 'hidden tax' on producers or consumers. We estimate the size of this tax and how it is affected by exogenous changes in larceny rates driven by the enactment of higher felony larceny thresholds. Pre-enactment hidden tax rates are small, ranging from 0.1 percent to 0.4 percent. These tax rates rise or fall with enactment, varying by product market. Such exogenous changes in the hidden tax induce state-level annual welfare changes that are minimal, ranging from -1,500 to 4,700 across product markets.
Keywords: K14; H20; D60; 330; larceny thresholds; crime; product markets; taxation; welfare